The Learning Outcomes of Swimming Using STAD Learning Model - Syahruddin, Syahruddin; Saleh, Muhammad Syahrul; Saleh, M Sahib (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This study aims to improve the learning outcomes of freestyle swimming through the STAD learning model in grade XI students of SMA Negeri 3 Bulukumba. This type of research is a type of class action research (PTK) Research is carried out for two cycles where each cycle consists of 2 meetings. Each meeting uses research procedures consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 31 students of grade XI MIPA.1 SMA Negeri 3 Bulukumba. The research instruments used are observation, evaluation tests, field notes, and documentation while the data collection techniques use observation techniques, test techniques, and documentation. The results showed that using the STAD learning model can improve freestyle swimming learning outcomes in students in Physical Education subjects.